Given : A linear equation is given to us . The equation is - ( 1 + 7x ) - 6 ( -7 - x ) = 36 .
To Find : The value of x .
Solution : The linear equation given to us is - ( 1 + 7x ) - 6 ( -7 - x ) = 36 . Let's simplify this step by step to find the value of x .
⇒ - ( 1 + 7x ) - 6 ( -7 - x ) = 36
![\red{\underline{\tt Step \:1- Open \:the\:brackets.}}]()
⇒ - 1 - 7x +42 + 6x = 36 .
![\red{\underline{\tt Step \:2- Group\: variables\:and\: constant\: terms.}}](https://img.qammunity.org/2021/formulas/mathematics/high-school/7nc0fg9krra1hcrh8nmod2mmiazs1xnjhq.png)
⇒ -7x + 6x -1 +42 = 36 .
![\red{\underline{\tt Step \:3- Transfer \: variables\:on\:one\: side\:\&\: constant\:terms\;on\: other\: side..}}](https://img.qammunity.org/2021/formulas/mathematics/high-school/blmpee7zdprpet3xia9x6y2fypmnqa0e4y.png)
⇒ -x = 36 - 41
⇒ - x = -5
⇒ x = 5 .
![\Large\boxed{\purple{\bf Value\:of\:x=5}}](https://img.qammunity.org/2021/formulas/mathematics/high-school/wgq1pvdepzftpec8a95f853gl58lq0thxa.png)